Pengaruh Penerapan Model Pembelajaran Berbasis Masalah Berbantuan Simulasi Interaktif Terhadap Hasil Belajar Fisika Siswa Kelas Viii Smpn 1 Pujut Tahun Pelajaran 2013/2014 - Winarni Listiawati; Gunawan Gunawan; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This research is a quasi-experimental aims to finding out the impact of problem-based learning model assist with interactive simulation of the results of learning physics of grade VIII SMPN 1 Pujut in academic year 2013/2014. The design of this research used of non-equivalent control group design, while the sampling technique used purposive sampling. The population ofÃÂ  this research is students of grade VIII SMPN 1 Pujut with 227 students, while the sampling are the students of grade VIII 1 as the experimental group and the students of grade VIII 6 as control group. The data result studying analyzed by t-test two tail using formulas polled variance. Obtain values thint = 2,519 and ttable =2,013 on degree of free is 47 with 5% significant degree. BecauseÃÂ  thint > ttable ,thenÃÂ  Ho will be rejected and Ha will be accepted which indicates that there is significant the impact of problem-based learning model assist with interactive simulation of the results of learning physics grade VIII SMPN 1 Pujut in academic year 2013/2014.